2015
DOI: 10.1051/0004-6361/201424709
|View full text |Cite
|
Sign up to set email alerts
|

SALT observations of southern post-novae

Abstract: Aims. We report on recent optical observations of the stellar and the nebular remnants of 22 southern post-novae. Methods. In this study, for each of our targets, we obtained and analysed long-slit spectra in the spectral range 3500-6600 Å and inResults. The changes in the emission lines' equivalent widths with the time since the outburst agree with earlier published results of other authors. We estimated an average value α = 2.37 for the exponent of the power law fitted to the post-novae continua. Our observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 108 publications
(242 reference statements)
3
28
0
1
Order By: Relevance
“…The optical spectrum (see Bianchini et al 1991, and Liu & Hu (2000) shows weak hydrogen and HeII 4686 emission lines. A recent SALT spectrum of GI Mon (Tomov et al 2015) also shows weak HeII 4686 and H-beta emission lines. The equivalent width of H-alpha suggests a moderately low inclination.…”
Section: Comments On the Inclination Of Individual Objectsmentioning
confidence: 98%
“…The optical spectrum (see Bianchini et al 1991, and Liu & Hu (2000) shows weak hydrogen and HeII 4686 emission lines. A recent SALT spectrum of GI Mon (Tomov et al 2015) also shows weak HeII 4686 and H-beta emission lines. The equivalent width of H-alpha suggests a moderately low inclination.…”
Section: Comments On the Inclination Of Individual Objectsmentioning
confidence: 98%
“…Tarasova & Shakhovskoi (2013) reported that the spectral energy distribution (SED) of their pre-maximum spectrum, taken on Aug. 15.8, was similar to a late-A or early-F-type spectrum. The line spectrum, which was dominated by P Cyg-type hydrogen lines with a pronounced absorption component (see Shore et al 2013a;Tomov et al 2013;Tarasova 2013;Munari et al 2013b), also suggested that the effective temperature of the envelope probably is 10 4 K. During Aug. 19, observed a significant weakening of the H i absorption components, while those of the Fe ii, He i, and O i profiles were still clearly present. This evolution indicated a distinctive cooling of the expanding envelope.…”
Section: Introductionmentioning
confidence: 94%
“…We have estimated that the flux loss due to the broad line wings and the limited width of the narrow band filters is less than 10% for both bands, using previous spectroscopic observations (Tomov et al 2015). Such loss is not relevant when compared to other uncertainties in our models.…”
Section: Line Fluxes and Dereddeningmentioning
confidence: 92%
“…The major and minor axes are 9.9 arcsec and 8.9 arcsec, respectively, with a mean value of 9.4 arcsec (see figure 2). Tomov et al (2015) measured an angular diameter of 12 arcsec for the shell from their Hα+[N II] narrow band imaging with Fabry-Perot Robert Stobie Spectrograph at SALT.…”
Section: Angular Diametermentioning
confidence: 99%
See 1 more Smart Citation